The Application of the Know-Meet-Share-Express Method to Improve Students’ Catholic Faith - Maria Stefania Ngura; Paulina Maria Ekasari Wahyuningrum; Emilianus Sember Sawo (Kirana Publisher (KNPub), 2026)
This study aims to describe the level of students Catholic faith knowledge before and after the application of the Know-Meet-Share-Express (KMSE) method from YOUCAT Indonesia, to describe its application in pastoral catechesis learning, and to test its effect on grade X students at SMAK St. Aloysius Palangka Raya. The study employed a quantitative approach with a quasi-experimental pretest-posttest control group design. The sample consisted of 56 students selected through simple random sampling, comprising 27 students in the experimental group taught with the KMSE method and 29 students in the control group taught with the conventional method. Data were collected through a 25-item multiple-choice test and a questionnaire, then analyzed using descriptive statistics and an independent samples t-test with SPSS 23. The results show that the experimental group mean rose from 49.48 to 78.07 (gain 28.59), while the control group rose only from 49.93 to 56.83 (gain 6.90). The t-test produced t = 10.160 with a significance of 0.000 (p < 0.05), so the null hypothesis was rejected. Questionnaire responses were also highly positive, ranging from 83.3% to 93.3% across the four stages. The study concludes that the KMSE method has a significant effect on improving students Catholic faith knowledge and offers a meaningful, transformative learning experience